El acoso de las fantasías - Žižek, Slavoj; López Martín, Francisco; Žižek, Slavoj (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2011)
Slavoj Žižek claims that the current age in which we live is plagued by fantasms in the form of digitized imagery and the increasingly abstract nature of daily life. He explores the relationship between fantasy and ideology.
Los siete velos de la fantasía -- ¿Amar al prójimo? ¡No, gracias! -- El fetichismo y sus vicisitudes -- El ciberespacio, o, La insoportable clausura del ser -- De lo sublime a lo ridículo : el acto sexual en el cine -- Robert Schumann : el antihumanista romántico -- La ley inconsciente : hacia una ética más allá del bien.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed May 13, 2016)
Keywords: Sociology; Fantasy; Concrete (Philosophy); Psychoanalysis and culture; Popular culture; Ideology; Virtual reality; Cyberspace; Electronic books